ZAKAT FUND MANAGEMENT STRATEGY FOR MUSTAHIK WELFARE MAQASHID SHARIA PERSPECTIVE - Muhammad Syafry Firman; I Isman; Muhammad Ammar Al Amudi; Prabu Arya Sembara (Profetika: Jurnal Studi Islam, 2023)
The purpose of this study is to explain the Management Strategy of Zakat Funds towards Mustahik in the Perspective of Maqashid Sharia Case Study at Baznas Samarinda City Prov. East Kalimantan. With the formulation of the problem: 1. What are the indicators used to identify Mustahik Faqir and Poor Groups who are entitled to receive Zakat funds? 2. How is the impact of acceptance and Zakat on Mustahik from the Faqir and Poor groups in the Maqashid Sharia perspective? This research is qualitatively descriptive with a sociological approach, data collection methods are observations, interviews and documentation at Baznas Samarinda City. Data analysis techniques are reducing data, presenting data, and drawing conclusions. The results showed that the Management Strategy of Zakat Funds Towards Mustahik in the Perspective of the Maqashid Sharia Case Study at Baznas Samarinda Prov. East Kalimantan. namely, the program is channelled into 5 programs: Samarinda Smart, Samarinda Healthy, Samarinda Empowered, Samarinda Berdakwah, and Samarinda Care by covering the fields of Economy, Health, Education, Da'wah, and Humanity. Indicators of zakat recipients used to determine the mustahik zakat categories of poor and poor, namely: a. Home/residence ownership index by looking at the condition of the house (roof, floor, walls), whether the family owns a house or not, the source of residential lighting. b. Ownership of assets including assets owned by families or individuals, local transportation owned, and facilities in accessing news/information. c. Income by looking at sources of income not exceeding 1,000,0000 and not having savings / high-value goods. The impact of the distribution of zakat funds on the welfare of mustahiq from the poor and poor groups in the maqashid sharia perspective is that the distribution of zakat funds is carried out in the form of consumptive zakat fund assistance, with this mustahiq program can increase their income which the percentage level of success is 80 per cent (%) as evidenced by surveys by Baznas Samarinda and information reports from the results of mustahiq businesses that experience profits and can meet their basic needs. Mustahiq has been able to independently change the status of mustahik to munfiq or muzakki through business capital assistance and business equipment assistance that has been provided by Bazas Samarinda City.